Long-term prognosis after out-of-hospital resuscitation of cardiac arrest in trauma patients: prehospital trauma-associated cardiac arrest. Issue 1 (26th October 2016) - Duchateau, François-Xavier; Hamada, Sophie; Raux, Mathieu; Gay, Matthieu; Mantz, Jean; Paugam Burtz, Catherine; Gauss, Tobias; ,
Abstract : Background: Although prehospital cardiac arrest (CA) remains associated with poor long-term outcome, recent studies show an improvement in the survival rate after prehospital trauma associated CA (TCA). However, data on the long-term neurological outcome of TCA, particularly from physician-staffed Emergency Medical Service (EMS), are scarce, and results reported have been inconsistent. The objective of this pilot study was to evaluate the long-term outcome of patients admitted to several trauma centres after a TCA. Methods: This study is a retrospective database review of all patients from a multicentre prospective registry that experienced a TCA and had undergone successful cardiopulmonary resuscitation (CPR) prior their admission at the trauma centre. The primary end point was neurological outcome at 6 months among patients who survived to hospital discharge. Results: 88 victims of TCA underwent successful CPR and were admitted to the hospital, 90% of whom were victims of blunt trauma. Of these 88 patients, 10 patients (11%; CI 95% 6% to 19%) survived to discharge: on discharge, 9 patients displayed a GCS of 15 and Cerebral Performance Categories (CPC) 1–2 and one patient had a GCS 7 and CPC of 3. Hypoxia was the most frequent cause of CA among survivors. 6-month follow-up was achieved for 9 patients of the 10 surviving patients. The 9 patients with a good outcome on hospital discharge had a CPC of 1 or 2 6 months post discharge. All returned to their premorbid family and social settings. Conclusions: Among patients admitted to hospital after successful CPR from TCA, hypoxia as the likely aetiology of arrest carried a more favourable prognosis. Most of the patients successfully resuscitated from TCA and surviving to hospital discharge had a good neurological outcome, suggesting that prehospital resuscitation may not be futile.